2010
DOI: 10.1038/leu.2009.293
|View full text |Cite
|
Sign up to set email alerts
|

Identification of activated Tnk1 kinase in Hodgkin's lymphoma

Abstract: To test this hypothesis, we extracted genomic DNA from one peripheral blood and 25 bone marrow samples of AML patients with t(8;21) from the University Medical Centers Freiburg, Germany and Nijmegen, The Netherlands. All patients had provided ethic board approved informed consent. The blast count in the peripheral blood sample was 35% and in bone marrow samples 470% in the majority of samples (range: 25-90%). In addition, to explore the mutation status in a homogeneous blast population, we investigated two AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 7 publications
2
26
0
Order By: Relevance
“…Among these peptides, we have fortunately found five IRF4 phosphorylation sites, including Y124, -176, -191, -180, and -427 (Table 1). Consistent with our results, phosphorylation of Y124 and Y427 and of Y191 of endogenous IRF4 was also identified by phosphoproteome profiling in Hodgkin's lymphoma cells (42) and multiple myeloma cells (41), respectively. In contrast, phosphorylation of Y37, Y121, and Y439, which were identified in Hodgkin's lymphoma cells (42), was not identified in EBV-transformed cells in our assays with the same strategy.…”
Section: Identification Of Irf4 Phosphorylation Sites Associated Withsupporting
confidence: 77%
See 2 more Smart Citations
“…Among these peptides, we have fortunately found five IRF4 phosphorylation sites, including Y124, -176, -191, -180, and -427 (Table 1). Consistent with our results, phosphorylation of Y124 and Y427 and of Y191 of endogenous IRF4 was also identified by phosphoproteome profiling in Hodgkin's lymphoma cells (42) and multiple myeloma cells (41), respectively. In contrast, phosphorylation of Y37, Y121, and Y439, which were identified in Hodgkin's lymphoma cells (42), was not identified in EBV-transformed cells in our assays with the same strategy.…”
Section: Identification Of Irf4 Phosphorylation Sites Associated Withsupporting
confidence: 77%
“…2). Although phosphorylation of Y61 has not been identified by phosphoproteome profiling, phosphorylation of Y124 has also been identified in Hodgkin's lymphomas (42). Thus, Y124 is a convincing phosphorylation site at least important for IRF4-associated lymphomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to LMP1 signaling, other unidentified lymphocyte-specific pathways may also impact the outcomes of IRF4 transcriptional activation, considering the following facts: (i) IRF4 is also phosphorylated in other contexts, such as human T-cell leukemia virus-1-infected cells, Hodgkin’s lymphoma cells 50 and multiple myeloma cells, 51 where LMP1 is absent; (ii) we have previously shown that, in addition to Src, other kinases including Alk and TNK also stimulate IRF4 transcriptional activity. 36 Thus, IRF4 may be activated through different lymphocyte-specific signaling pathways that involve distinct kinases in different contexts; (iii) in the context of EBV latent infection, in addition to LMP1, LMP2A also activates the PI3K/Akt pathway in response to BCR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Since both cytoplasmic localizations could be observed in untransfected cells lines expressing the wild type form of the protein, it is tempting to speculate that the subcellular distribution of PARP12 may be regulated by a signaling event leading to the post-translational modification of the N-terminal domain of the protein. Accordingly, several studies have identified PARP12-derived N-terminal peptides displaying phosphorylated residues (61,62). PARP12 may therefore represent an ISG with dual functional properties both of which may contribute to the establishment of an antimicrobial state in cells exposed to IFNs.…”
Section: Discussionmentioning
confidence: 99%